Diverse responses of wild and cultivated tomato to BABA, oligandrin and Oidium neolycopersici infection - Satková, Pavla (Ann Bot, 2017)
Background and Aims Current strategies for increased crop protection of susceptible tomato plants against pathogen infections include treatment with synthetic chemicals, application of natural pathogen-derived compounds or transfer of resistance genes from wild tomato species within breeding programmes. In this study, a series of 45 genes potentially involved in defence mechanisms was retrieved from the genome sequence of inbred reference tomato cultivar Solanum lycopersicum ‘Heinz 1706’. The aim of the study was to analyse expression of these selected genes in wild and cultivated tomato plants contrasting in resistance to the biotrophic pathogen Oidium neolycopersici, the causative agent of powdery mildew. Plants were treated either solely with potential resistance inducers or by inducers together with the pathogen. Methods The resistance against O. neolycopersici infection as well as RT-PCR-based analysis of gene expression in response to the oomycete elicitor oligandrin and chemical agent β-aminobutyric acid (BABA) were investigated in the highly susceptible domesticated inbred genotype Solanum lycopersicum ‘Amateur’ and resistant wild genotype Solanum habrochaites. Key Results Differences in basal expression levels of defensins, germins, β-1,3-glucanases, heveins, chitinases, osmotins and PR1 proteins in non-infected and non-elicited plants were observed between the highly resistant and susceptible genotypes. Moreover, these defence genes showed an extensive up-regulation following O. neolycopersici infection in both genotypes. Application of BABA and elicitin induced expression of multiple defence-related transcripts and, through different mechanisms, enhanced resistance against powdery mildew in the susceptible tomato genotype. Conclusions The results indicate that non-specific resistance in the resistant genotype S. habrochaites resulted from high basal levels of transcripts with proven roles in defence processes. In the susceptible genotype S. lycopersicum ‘Amateur’, oligandrin- and BABA-induced resistance involved different signalling pathways, with BABA-treated leaves displaying direct activation of the ethylene-dependent signalling pathway, in contrast to previously reported jasmonic acid-mediated signalling for elicitins.